Stochastic logicallinguistic approachMulti-level automated object’s dialogue control (MADC) - Dayoub, Yaroub (Latakia University Journal -Engineering Sciences Series, 2015)
Object’s supportingmulti-leveladaptive dynamic dialogue scenario depends on eliminatinguselessobject’s transmission between and through differentlevel’s stepsand building an object’s module which reflects all it’s parameters(evaluation criteria , failed or successful tries intensity for solving problems, visit number of each dialog level , step expired time at different levels etc.)taking in consideration all passed steps and issues an order to transfer the dialogue from one step to another depending on evaluated object’s activity at current step and at all passed steps at different levels,so minimize lost time required to execute useless operations and unsuitable dialogue scenario demonstration, and minimizethe dialogue time and so increasing dialogue efficiency .For registering and recognizing object’s activities and parameters it’s good touselinguisticapproachusing non-context-free formal grammar (type .1-regarding toChomsky’s classification), so having viewed number of grammar’s productionscan begenerate asuitableenough number of symbolic string for registering and recognizingobject’s activities then selecting the suitable next dialogue scenario and effective controlofcomplex object’s motion and permits to construct multi-leveladaptive dynamic dialogue system.Adaptive dialogue depends on modeling object’sdialogueand building twoobject’s modules: step object’s module (object’s activities in range one step) andcurrent object’s module (object’s activities history at all dialogue levels -passed path).